Xanthine oxidase inhibitory effects of the constituents of Chrysanthemum morifolium stems. (March 2017) - Qu, Lu; Ruan, Jing-Ya; Jin, Li-Jun; Shi, Wen-Zhong; Li, Xiao-Xia; Han, Li-Feng; Zhang, Yi; Wang, Tao
Graphical abstract: Highlights: Four new compounds and 27 known ones were isolated from stems of C. morifolium. Nine compounds displayed significant inhibitory activities on xanthine oxidase. The structure-activity relationship of compounds was discussed. Abstract: The flowers of Chrysanthemum morifolium Ramat. (family: Asteraceae) are used in Traditional Chinese Medicine to treat fever, cold and swelling. However the aerial part is considered as agriculture waste and the chemical and pharmacological information is scanty. From the stems of this plant, four new compounds named as morineoliganosides A (1 ), B (2 ), C (3 ) and heterophyllol-1- O - β -d -glucopyranoside A (4 ) together with 27 known isolates (5–31 ), including flavonoids and caffeoylquinic acids were isolated. Their structures were elucidated by chemical and spectroscopic methods The inhibitory effects on xanthine oxidase of these compounds have been determined. This research provided a scientific development and utilization of C. morifolium stems.